Carbapenemase-producing Enterobacterales causing secondary infections during the COVID-19 crisis at a New York City hospital. (17th November 2020) - Gomez-Simmonds, Angela; Annavajhala, Medini K; McConville, Thomas H; Dietz, Donald E; Shoucri, Sherif M; Laracy, Justin C; Rozenberg, Felix D; Nelson, Brian; Greendyke, William G; Furuya, E Yoko; Whittier, Susan; Uhlemann, Anne-Catrin
Abstract: Background: Patients with COVID-19 may be at increased risk for secondary bacterial infections with MDR pathogens, including carbapenemase-producing Enterobacterales (CPE). Objectives: We sought to rapidly investigate the clinical characteristics, population structure and mechanisms of resistance of CPE causing secondary infections in patients with COVID-19. Methods: We retrospectively identified CPE clinical isolates collected from patients testing positive for SARS-CoV-2 between March and April 2020 at our medical centre in New York City. Available isolates underwent nanopore sequencing for rapid genotyping, antibiotic resistance gene detection and phylogenetic analysis. Results: We identified 31 CPE isolates from 13 patients, including 27 Klebsiella pneumoniae and 4 Enterobacter cloacae complex isolates. Most patients (11/13) had a positive respiratory culture and 7/13 developed bacteraemia; treatment failure was common. Twenty isolates were available for WGS. Most K. pneumoniae (16/17) belonged to ST258 and encoded KPC (15 KPC-2; 1 KPC-3); one ST70 isolate encoded KPC-2. E. cloacae isolates belonged to ST270 and encoded NDM-1. Nanopore sequencing enabled identification of at least four distinct ST258 lineages in COVID-19 patients, which were validated by Illumina sequencing data. Conclusions: While CPE prevalence has declined substantially in New York City in recent years, increased detection in patients with COVID-19 may signal a re-emergence of these highly resistant pathogens in the wake of the global pandemic. Increased surveillance and antimicrobial stewardship efforts, as well as identification of optimal treatment approaches for CPE, will be needed to mitigate their future impact.